A Rare Variation of Transverse Testicular Ectopia (TTE) in a Young Adult as an Incidental Finding during Investigation for Testicular Pain - Chrysovalantis Gkekas; Evangelos N. Symeonidis; Ioannis Tsifountoudis; Christos Georgiadis; Vasileios Kalyvas; Apostolos Malioris; Michail Papathanasiou (Case Reports in Urology)
Transverse testicular ectopia (TTE) with fused vas deferens is an extremely rare clinical entity. Herein, we present a case of a 19-year-old patient with persistent left testicular pain lasting for a week. Clinical examination revealed an empty right hemiscrotum, a normal left-sided descended testis, and in close proximity a mass-like structure resembling testicular parenchyma. Laboratory tests were significant for elevated follicle-stimulating hormone (FSH), while sperm count revealed azoospermia. Ultrasound imaging (US) of the scrotum demonstrated the presence of both testes in the same left hemiscrotum with varicocele and no signs of inguinal hernia. Magnetic resonance imaging (MRI) of the penis and scrotum revealed TTE with a single, fused vas deferens, and hypoplastic seminal vesicles. Surgical intervention by means of microsurgical sperm retrieval and transseptal orchidopexy were considered but not performed, primarily owing to the patient’s unwillingness and to a lesser extent due to the restriction that the short and fused vas would pose in an attempt to transpose the ectopic testis. Therefore, an annual follow-up was recommended.